If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -12 = 2y + -14 Reorder the terms: -12 + -4y = 2y + -14 Reorder the terms: -12 + -4y = -14 + 2y Solving -12 + -4y = -14 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -12 + -4y + -2y = -14 + 2y + -2y Combine like terms: -4y + -2y = -6y -12 + -6y = -14 + 2y + -2y Combine like terms: 2y + -2y = 0 -12 + -6y = -14 + 0 -12 + -6y = -14 Add '12' to each side of the equation. -12 + 12 + -6y = -14 + 12 Combine like terms: -12 + 12 = 0 0 + -6y = -14 + 12 -6y = -14 + 12 Combine like terms: -14 + 12 = -2 -6y = -2 Divide each side by '-6'. y = 0.3333333333 Simplifying y = 0.3333333333
| -9(x-1)=9-9x | | 10=7x-6 | | 2-2a=-3(-6+6a)+8a | | -5+9n+6=0 | | -12abc+2abc-8A= | | 7x-5y+3x-2y= | | -3(2s-5)-15=-2(6s+4)-2 | | u+3=9 | | 5a*5ab= | | 2+y+1=5 | | 4(2x+-1)+6=8x+-4 | | 4(2x+-1)+6=8x+-3 | | 3/7x42/14 | | 1.80=n/100(30) | | n+4-9-5n=0 | | -2(y-6)=y+3+2y | | 4x-5/3-7x=4 | | -9=-177n | | Y^3=9 | | n+4-9-5=0 | | -3x+7=5-(8x+4) | | t=225+0.02(325) | | 19n+17=14n-13 | | 3x+62=3x-9 | | t=200+25+.02x | | 5-(6-(3-(7+3)))= | | 4.2+3.9+5+x=21.5 | | X+11=3x+62 | | 25+8k=3(8+3k)-7 | | 5x-13=-27 | | x+11=3x-9 | | -11r-12r=0 |